Does Fruit and Vegetable Consumption During Adolescence Predict Adult Depression? A Longitudinal Study of US Adolescents - Hoare, Erin; Hockey, Meghan; Ruusunen, Anu; Jacka, Felice N. (Frontiers in Psychiatry, 2018)
The relationship between better diet quality and decreased depression across the life span is consistent and compelling. Fruit and vegetable consumption has been of particular interest. The nutritional benefits from the consumption of fruits and vegetables may mitigate non-communicable diseases and promote brain and mental health. This study aimed to determine whether fruit and vegetable consumption during adolescence was associated with a reduced risk of developing depression in adulthood in a large, representative sample of US individuals. Data from the Add Health Study were analysed, which included 3,696 participants who were aged approximately 17 years at baseline (1994-1995), and 29 years at follow-up (2007-2008). The Center for Epidemiologic Studies Depression Scale was used to assess depression and a self-report item asked how many times the participant consumed fruit/vegetables on the previous day. Individuals who were depressed at both times points had the highest proportion who failed to consume any fruit (31%) or vegetables (42%) on the previous day. Fruit and vegetable consumption did not predict adult depression in fully adjusted models. Cross-sectional associations existed for diet and adolescent depression only. Our findings offer weak support for fruit and vegetable consumption as being protective against adult depression. Future research will benefit from more precise measures of dietary intakes.